Uruguayan secondary school students speak up about tobacco: results from focus group discussions in and around Montevideo. (June 2019) - Peterson, Erin; Harrell, Melissa; Springer, Andrew; Medina, José; Martinez, Lucía; Perry, Cheryl; Estol, Diego
This qualitative research study investigated intrapersonal, interpersonal, and environmental factors that shape young adolescent tobacco use behaviors in Uruguay. Focus groups were conducted in the summer of 2012 and fall of 2013 in four secondary schools in Montevideo, Uruguay, including two private schools and two public schools. A total of four focus groups were led in each school, composed of 4–6 students each, 16 focus groups in total. Data analysis utilized NVivo software and included deductive and inductive content analysis. Overwhelmingly, students reported that the onset of smoking occurred in the second year of secondary school. The primary intrapersonal factors that were found to be universal among respondents identified that smoking was a performance in groups, to garner attention from their peers. Students interviewed most often stated that the greatest interpersonal factors for smoking were to look older, as a rite of passage, and for group membership. Environmental factors cited most often indicate that they smoked during unsupervised time, either at night or around the short Uruguayan school day. Focus group interviews revealed that adolescents had easy access to cigarettes for purchase through small family owned grocery stores, even though laws exist preventing the sale of cigarettes to minors. Few differences were cited between strata related to cigarette use in adolescents. The differences that do exist are most apparent across gender, though there were a few observed differences when stratified by public and private school. Findings from this study indicate that key factors across ecological levels (intrapersonal, interpersonal, and environmental) should be taken into consideration when designing tobacco prevention programs for youth in Uruguay. A multiple-component approach which addresses risk factors at all of these levels, implemented in schools, may be particularly well-suited to this setting.